Analisis Tahapan Sistem Rekrutmen dan Seleksi Pengemudi PT Banyumas Raya Transportasi - Ira Amalia Fadillah; Andriya Oktanita; Alfizi Alfizi; Puspita Lianti Putri; Slamet Slamet; April Kurniawan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study analyzes the recruitment and selection system for drivers at PT Banyumas Raya Transportasi. The focus of this research is to identify weaknesses in the existing system and formulate strategic recommendations to enhance the effectiveness of the recruitment and selection process. The research method used is qualitative descriptive, with primary data obtained through interviews with the HRGA division and secondary data from company documents and relevant literature. The findings indicate a high turnover rate and inefficiencies in the recruitment methods, which still rely heavily on traditional approaches such as social media and bulletin boards. To address these issues, this study recommends implementing a digital recruitment system, diversifying recruitment methods, and adopting competency-based selection processes to improve recruitment efficiency and effectiveness. The results of this research are expected to assist the company in developing a more sustainable and competitive workforce.